HUBUNGAN ASPEK POWER, PENERAPAN SISTEM PENGENDALIAN ADMINISTRATIF, AKUNTABILITAS, DAN EFISIENSI PROGRAM JAMINAN KESEHATAN - Prayudi, Made Aristia; Basuki, Hardo (UI Scholars Hub, 2014)
This study aims to investigate the effect of various aspects of power on administrative control system implementation, i.e. the Standard Operating Procedure (SOP) of a local health insurance program, as well as on its organizational consequences in the form of accountability and efficiency. The sequential explanatory strategy of mixed methods research is then used. Data from 86 physicians of 7 local public hospitals in Bali Province collected through survey using self-report questionnaires at quantitative stage and the transcript of an interview process conducted on qualitative stage was analyzed using Partial Least Square (PLS) and descriptive statistical technique, respectively. The results show that external pressure in the form of legal requirements significantly influences this type of administrative control system implementation. Moreover, the implementation of administrative control system is also shown to have a positive impact on accountability, while accountability itself displays full mediating effect on the positive relationship between the implementation of administrative control systems and efficiency.